2023
DOI: 10.1002/solr.202201115
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Hydrothermal Sulfuration Strategy toward Effective Defect Passivation Enabling 6.92% Efficiency Sb2S3 Solar Cells

Abstract: Chalcogenide-based solar cells, such as Cu(In,Ga)(S,Se) 2 (CIGSSe), [1] CdTe, [2] Cu 2 ZnSn(S,Se) 4 (CZTSSe), [3,4] CuSb(S, Se) 2 , [5] NaSbS 2 , [6] AgBiS 2 , [7] SnS, [8] GeSe, [9] and Sb 2 (S,Se) 3 , [10,11] are emerging photovoltaic systems with great application potential. Currently, the record efficiencies of CIGSSe and CdTe photovoltaic devices are over 22%. [12] Furthermore, the certified efficiencies of CZTSSe [3] and Sb 2 (S,Se) 3 [13] solar cells have achieved ≥10% efficiencies. Besides, CZTS [14,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This result indicated that the Sb 2 S 3 -S-TF device had a reduced probability of charge recombination and improved efficiency of charge transfer, improving the photovoltaic performance of the device. 57…”
Section: Comparison Of the Photovoltaic Performances Of The Devicesmentioning
confidence: 99%
“…This result indicated that the Sb 2 S 3 -S-TF device had a reduced probability of charge recombination and improved efficiency of charge transfer, improving the photovoltaic performance of the device. 57…”
Section: Comparison Of the Photovoltaic Performances Of The Devicesmentioning
confidence: 99%
“…Huang et al 77 demonstrated a novel (NH 4 ) 2 S-induced hydrothermal sulfurization process for the fabrication of Sb 2 S 3 solar cells. (NH 4 ) 2 S undergoes hydrolysis to produce H 2 S, a strong sulfurization agent.…”
Section: Defects In Sb2x3 Materials and Their Implication In The Perf...mentioning
confidence: 99%
“…96 However, recent studies suggest that controlled O 2 -incorporation can help in passivating bulk and interface defects, improving the device performance. 97 In addition, in situ sulfurization, 98,99 post-deposition thioacetamide (TA) treatment, 78 ammonium sulfide ((NH 4 ) 2 S) treatment, 77 thiourea (TU) treatment, 5 selenization, 100–102 alkali-metal doping, 103–105 and alcohol-vapor annealing 106 are key strategies to passivate deep-defects and boost the PCE of Sb 2 X 3 solar cells.…”
Section: Strategies Toward High Pce Sb2x3 Solar Cellsmentioning
confidence: 99%
“…[31] Huang et al introduced tartaric acid additives in the hydrothermal deposition process of Sb 2 S 3 to achieve in situ sulfurization and optimized the hydrothermal sulfurization process by using (NH 4 ) 2 S, achieving efficiencies of 6.31 and 6.92%, respectively. [32,33] Zeng et al manufactured Sb 2 S 3 films from a raw stibnite source and removed surficial oxides by the sulfurization process. [34] At present, it is reported that the sulfur sources used to treat Sb 2 S 3 absorbers include sulfur powder, thioacetamide (TA), H 2 S, thiourea (TU), and ammonium sulfide ((NH 4 ) 2 S).…”
mentioning
confidence: 99%
“…[34] At present, it is reported that the sulfur sources used to treat Sb 2 S 3 absorbers include sulfur powder, thioacetamide (TA), H 2 S, thiourea (TU), and ammonium sulfide ((NH 4 ) 2 S). [31][32][33][35][36][37][38] Surface sulfurization and selenization can improve the back interfacial quality and fill factor, [35,39] which mainly acting on the surface. However, the S element makes it difficult to enter the bulk of crystalized Sb 2 S 3 films by surface sulfurization.…”
mentioning
confidence: 99%